Lessons learned from the first evaluation of the Medical Insurance for a New Generation: bridging research and policy Lecciones aprendidas de la primera evaluación del Seguro Médico para una Nueva Generación - Ricardo Pérez-Cuevas; Salomón Chertorivski; Gabriel Cortés-Gallo; Evelyne Rodríguez-Ortega; Francisco Caballero; Onofre Muñoz-Hernández (Instituto Nacional de Salud Pública, 2012)
The first evaluation of the Medical Insurance for a New Generation program (SMNG) was conducted in 2009. A mixed-method approach was used to obtain a comprehensive picture of SMNG members and the program itself. The evaluation comprised: 1) Program design; 2) Social and health conditions of its members; 3); Evaluation of SMNG's performance by measuring coverage, productivity and efficiency; 4) Families health expenditures. The lessons learned for the program are that SMNG is focused on a vulnerable segment of the population with pervasive unmet health needs; prevalence of malnutrition, anemia and other conditions remains high. Further efforts are necessary to deploy the program where it is most needed, particularly in rural areas; most of its members are urban dwellers. However, more needs to be done to educate members about the importance of preventive care and to build the capability of health providers to provide high quality care. Families are still experiencing hardship to provide medical care to their children, so additional efforts are needed to decrease out-of-pocket and catastrophic expenditures. The lessons learned for the evaluation allow concluding that this first evaluation set the groundwork for better-targeted subsequent interventions and evaluations aimed at showing the impact of SMNG to bridge existing gaps in equity, access, coverage, and health status of Mexican children. La primera evaluación del Seguro Médico para una Nueva Generación (SMNG) se llevó a cabo en 2009. La evaluación utilizó métodos mixtos para obtener una imagen completa de los miembros del SMNG y del programa. La evaluación comprendió: 1) el diseño del programa, 2) las condiciones sociales y de salud de los miembros, 3) acceso y uso de los servicios de salud, 4) la calidad de los servicios de atención ambulatoria y hospitalaria y 5) el efecto en los gastos de salud de las familias. El SMNG está enfocado a la población vulnerable con necesidades de salud no satisfechas, donde persiste la prevalencia de la desnutrición, anemia y otras enfermedades. Son necesarios esfuerzos adicionales para aumentar la cobertura del programa en zonas rurales donde la necesidad es mayor; pues la mayoría de sus miembros habitan en áreas urbanas, también es indispensable fortalecer la atención preventiva y fortalecer la capacidad de los proveedores de salud para proporcionar atención de alta calidad. Las familias todavía están experimentando dificultades para prestar atención a sus hijos, son necesarios esfuerzos adicionales para disminuir los gastos de bolsillo y catastrófico. Esta primera evaluación establece las bases para intervenciones y evaluaciones posteriores sustentadas en objetivos mejor definidos y enfocados a demostrar que SMNG está disminuyendo las brechas existentes en equidad, acceso, cobertura y estado de salud de la niñez mexicana.